‘We asked for life!’: women’s prison zines in 1970s America - Wright, Olivia (2017)
This dissertation discusses the previously unexamined and little-acknowledged genre of women’s prison zines in America. Beginning in the 1930s, these works of art and literature gave insight into the invisibilised world of women’s prisons and challenged preconceived ideas and stereotypes about female incarceration. The genre reached a peak in the 1970s—the decade on which I focus. Establishing the genre and its core characteristics for the first time, I define women’s prison zines as a form of “collective outsider writing” and place them into key theoretical and academic contexts that otherwise exclude them. Chapter One defines women’s prison zines as a distinctive and compelling subgenre of American protest literature, with a complex protest aesthetic aimed at wider social change beyond penal reform. Chapter Two goes one step further to place zines within the feminist protest writing tradition. The zines offer a concentrated perspective on women’s rights through collaboration with external feminist organisations and discussion of gendered concerns. Finally, Chapter Three argues that women’s prison zines develop the tradition of feminist collective autobiography, as they offer a powerful, collective narrative voice that establishes solidarity and kinship in an otherwise confined and alienating space. I argue that women’s prison zines sit at the intersection of these three genres—protest literature, feminist writing and collective autobiography—and that they fuse together elements of all three traditions to form a key example of what I term “collective outsider writing.”